2022
DOI: 10.3389/fimmu.2022.1022420
|View full text |Cite
|
Sign up to set email alerts
|

A necroptosis related prognostic model of pancreatic cancer based on single cell sequencing analysis and transcriptome analysis

Abstract: BackgroundAs a tumor type with high mortality and poor therapeutic effect, the pathogenesis of pancreatic cancer is still unclear. It is necessary to explore the significance of necroptosis in pancreatic cancer.MethodsPancreatic cancer transcriptome data were obtained from the TCGA database, ICGC database, and GSE85916 in the GEO database. The TCGA cohort was set as a training cohort, while the ICGC and GSE85916 cohort were set as the validation cohorts. Single-cell sequencing data of pancreatic cancer were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Kaplan-Meier survival analysis demonstrated a significantly worse prognosis for patients classified in the high-risk group in contrast to those in the low-risk group. Furthermore, the ROC curve indicated AUC values of 0.73, 0.81, and 0.81 for 1-, 3-, and 5-year OS, respectively, suggesting that the risk model outperformed previous reports [35,36]. Additionally, the model was validated as a robust prognostic biomarker for PAAD across three independent cohorts.…”
Section: Discussionmentioning
confidence: 67%
“…Kaplan-Meier survival analysis demonstrated a significantly worse prognosis for patients classified in the high-risk group in contrast to those in the low-risk group. Furthermore, the ROC curve indicated AUC values of 0.73, 0.81, and 0.81 for 1-, 3-, and 5-year OS, respectively, suggesting that the risk model outperformed previous reports [35,36]. Additionally, the model was validated as a robust prognostic biomarker for PAAD across three independent cohorts.…”
Section: Discussionmentioning
confidence: 67%
“…The results indicated that NKCMGS had an impact the prognosis of PDAC patients in each clinical subgroups, which indicates a good prognostic value of NKCMGS. NKCMGS has higher stability and ability to identify high-risk patients compared to the model constructed by Zhang et al based on neuroendocrine, metabolism-related genes and the iron death-related signature constructed by Chen et al 42 , 43 .…”
Section: Discussionmentioning
confidence: 97%
“…In previous investigations, several regulated cell death-related predictive signature have been reported in kinds of carcinoma, including pancreatic carcinoma. In combination with single-cell sequencing analysis and transcriptome analysis, a necroptosis-related signature consisting of POLR3GL, COL17A1, DDIT4, PDE4C, CLDN1, HMGA2, CENPF, and EPS8 had been constructed to predict pancreatic carcinoma prognosis (10). In addition, 14 ferroptosis-related genes were identi ed to establish a prognostic signature (11).…”
Section: Discussionmentioning
confidence: 99%